New crickets of the subfamilies Phaloriinae and Pteroplistinae (Orthoptera: Gryllidae) from Singapore - Gorochov, Andrej V.; Tan, Ming Kai (Zootaxa, 2012)
Three new species of Phaloriinae [Trellius (Protrellius) neesoon sp. n., Tremellia timah sp. n., Phaloria? jerelynae sp. n.] and a new genus with a new species of Pteroplistinae [Singapuriola separata gen. et sp. n.] are described from Singapore. So, the southern part of Malacca is here indicated as a most western locality for the genus Tremellia Stål and possibly for the genus Phaloria Stål (except the widely distributed Phaloria insularis Bolívar).